The effect of heat input in multi-pass GMAW of S960QL UHSS based on weaving and stringer bead procedure on microstructure and mechanical properties of HAZ - Mert, Tolga; Gurol, Ugur; Tumer, Mustafa (IOP Publishing Ltd, 2023)
Quenched and tempered S960QL (yield strength & GE; 960 MPa) ultra-high strength steel (UHSS) thick plates were joined by multi-pass robotic gas metal arc welding (GMAW) using weaving and stringer bead techniques. The effects of microstructural changes in heat-affected zone (HAZ) of the joint on toughness and hardness were examined. Weaving and stringer bead techniques applied for the multi-pass welding procedure altered average peak temperatures and exposure time to those temperatures. Mechanical properties of HAZs were evaluated by utilizing notch impact and hardness tests, and these results were correlated with microstructural characterizations using optical (OM) and scanning electron microscopes (SEM). Prior austenite grain (PAG) coarsening occurred because of increased exposure time to peak temperature in coarse-grained HAZ (CGHAZ) of the W-5 (weaving pass) joint. CGHAZs at the face pass, which have not been subjected to a second thermal cycle, have the highest hardness in both joints. Hardness of SCHAZ and CGHAZ of S-12 joint was 7% and 1% higher compared with W-5 joint, respectively. Weld metal hardness of W-5 joint was 15% lower than that of S-12 joint. Both joints not only fulfilled the requirements of minimum 50 J per EN ISO 10025-6 at -20 & DEG;C but exceeded this limit by 50% (W-5) and 200% (S-12). Lateral expansions for impact toughness specimens were around 17.5% for S-12 joint, whereas it was 4% for W-5 joint. Since HAZ in the S-12 (stringer bead) joint is narrow compared with the one in the W-5 joint, impact toughness values were higher with the S-12 joint due to the locations of the notches of the impact specimens.
Keywords: S960QL; GMAW; weaving; stringer pass; HAZ; mechanical properties; microstructure; MARTENSITE-AUSTENITE CONSTITUENT; AFFECTED ZONE HAZ; CRACK INITIATION; STRENGTH; STEEL; TOUGHNESS; PROPAGATION; Materials Science